CD4 T cell subsets - Stockinger, Brigitta (Henry Stewart Talks, 2020)
CD4 T cell effector specialisation in the periphery, Influence of cytokines and transcription factors, Th1 and Th2 paradigm extended with new subsets Treg, Th17 and Tfh, Plasticity of effector functions, Functional consequences of plasticity